2015
DOI: 10.3899/jrheum.141513
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Involvement in Granulomatosis with Polyangiitis

Abstract: Objective To determine frequency and outcomes of granulomatosis with polyangiitis (GPA)–related cardiac disease in a North American GPA cohort. Methods Analysis was done of all patients in the Vasculitis Clinical Research Consortium Longitudinal Study of GPA. Demographic and clinical characteristics of patients with and without GPA-related cardiac involvement were compared. Results Of 517 patients with GPA, 3.3% had cardiac involvement. No differences were observed between patients with or without cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 10 publications
0
78
0
5
Order By: Relevance
“…In a large-scale retrospective review, Walsh et al 7 reported that 5.7% of 535 patients with newly diagnosed GPA had cardiovascular clinical findings, and that these patients had a significantly higher rate of disease relapse than patients without cardiac disease. Separately, McGeoch et al 2 found that 3.3% of patients with GPA had associated cardiac findings; the most common manifestations were pericarditis and cardiomyopathy, while only two patients in the cohort (0.4%) had coronary artery involvement. All patients with cardiac disease in this series presented with cardiopulmonary symptoms, including chest pain, dyspnoea and syncope; these patients did not have higher rates of mortality or disease relapse.…”
Section: Discussionmentioning
confidence: 97%
“…In a large-scale retrospective review, Walsh et al 7 reported that 5.7% of 535 patients with newly diagnosed GPA had cardiovascular clinical findings, and that these patients had a significantly higher rate of disease relapse than patients without cardiac disease. Separately, McGeoch et al 2 found that 3.3% of patients with GPA had associated cardiac findings; the most common manifestations were pericarditis and cardiomyopathy, while only two patients in the cohort (0.4%) had coronary artery involvement. All patients with cardiac disease in this series presented with cardiopulmonary symptoms, including chest pain, dyspnoea and syncope; these patients did not have higher rates of mortality or disease relapse.…”
Section: Discussionmentioning
confidence: 97%
“…Churg-Strauss syndrome has been associated with cardiac manifestations with one study indicating a prevalence of 3.3% in North American centres 1. Other studies investigating cardiac involvement using ECG, echocardiogram and cardiac MRI showed higher incidence 2.…”
Section: Discussionmentioning
confidence: 99%
“…However, in North America cohort cardiac involvement was not associated with a higher rate of mortality or relapse of vasculitis, but the frequency of cardiac involvement was much lower in this group than in European cohorts [16].…”
Section: Cardiac Manifestation In Granulomatosis With Polyangiitismentioning
confidence: 97%
“…Estimates of the frequency of cardiac involvement in GPA vary widely, with a North American study reporting a rate of 33.3% and no association with a higher rate of relapse or premature death [16], while a European study reported cardiac involvement in 46% of GPA patients assessed with electrocardiography and echocardiography, along with increased all-cause and cardiovascular mortality [18].…”
Section: Cardiac Manifestation In Granulomatosis With Polyangiitismentioning
confidence: 99%